(3cJGH aj TQM GdCMGOjK GdfHhjIs - (3eLghds
(3ChdgG (B:s
(3Chd GdehLhO efg bhdg GQMehG YRjR bhe Pd hZfjkG GaJbQ hYGdekG Hjf LgGd hbGd ai GdOQQ hCNQLI GHf MjGf ai JGQjNg s
(3BNQgG (B:s
(3BNQ GdehLhO efg bhdg GdGMGOjK ai ef eGJ dGjTQc HGddg TjFkG ONd GdLfI cKjQI efgG GdTjNjf Yf GHf eSYhO hefgG eGdSde Yf YKeGf QVi Gddg Yfg hbGd GdbGQF eYfGg UMjM dbhdg s
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3JHUQGJ GdCUd (B:s
(3GdfSNI fGbUI GdChd , eHJhQI GdBNQ s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdMOjK h GdeUWdMs